(untitled) (Eurasian Research Bulletin, 2023)
The validity of this article and its relevance are justified by the role played by the text, especially fiction, as an object of humanitarian and philological research and thinking. The ability to interpret a text, as many researchers rightly note, allows you to join the author’s vision of the world, enrich yourself spiritually, and improve a person’s spiritual culture. When analyzing a literary text, the dominant place is usually given to lexical and stylistic means, but syntactic means, which have come to the forefront in modern literature, play a crucial role in creating the expressiveness of the text, in understanding the main idea of the work and the author’s worldview.